Pengaruh Rotasi Auditor, Audit Tenure, dan Ukuran KAP terhadap Kualitas Audit Dimoderasi Audit Fee - Ronid Ramadhan; Mhd. Karya Satya Azhar (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to determine the effect of auditor rotation, audit tenure, and public accounting firm size on audit quality with audit fees as a moderating variable, in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This study study quantitative method using a population of manufacturing companies in the consumer goods industry listed on the IDX. Sampling using purposive sampling technique so that the number of samples in this study was 370. The data analysis used is moderated regression analysis (MRA) with the EViews 12 data processing application. The results of the study show that auditor rotation does not affect audit quality, audit tenure does not affect audit quality, while the size of the public accounting firm has a positive effect on audit quality. In addition, audit fees cannot moderate the effect of auditor rotation on audit quality, audit fees cannot moderate the effect of audit tenure on audit quality, and audit fees cannot moderate the effect of the size of the public accounting firm on audit quality.